Operational Audit Analysis on Credit and Receivable Sales at PT. Penerbit Erlangga Mahameru Palembang Branch - Sawitri, Riska Agi; Prasetyo, Ferry (Utan Kayu Publishing, 2022)
Sales are significant and decisive marketing functions of a company to achieve its objectives and to make profits. Sales, the main revenue makers of a company, need good internal control in order to avoid fraud or manipulation. This study aimed at analyzing the internal control of credit and receivable sales at PT. Penerbit Erlangga Mahameru, Palembang Branch in order to get a clear picture of the application of the internal control. This is a field study taking place at the company as an object of this study by using descriptive qualitative method in the form of oral or written words of observable human behavior. The data of the study were gathered by interviews, observations, documentations, literature reviews, and data validities.